Mast cells and angiogenesis in gastric carcinoma - Ribatti, Domenico (Blackwell Publishing Ltd, 2010)
Previous studies have shown that increased vascularity is associated with haematogenous metastasis and poor prognosis in gastric cancer. The role of mast cells in gastric cancer angiogenesis has not been clarified completely. In this study, we correlated microvascular density and tryptase- and chymase-positive mast cells with histopathological type in gastric cancer. Specimens of primary gastric adenocarcinomas obtained from 30 patients who had undergone curative gastrectomy were investigated immunohistochemically by using anti-CD31 antibody to stain endothelial cells and anti-tryptase and anti-chymase antibodies to stain mast cells. The results showed that stage IV gastric carcinoma has a higher degree of vascularization than other stages and that both tryptase- and chymase-positive mast cells increase in parallel with malignancy grade even if the density of chymase-positive mast cells was significantly lower than the density of tryptase-positive mast cells and is highly correlated with the extent of angiogenesis. This study has demonstrated that mast cell density correlates with angiogenesis and progression of patients with gastric carcinoma. Understanding the mechanisms of gastric cancer angiogenesis provides a basis for a rational approach to the development of an antiangiogenic therapy in patients with this malignancy.